In-Situ FTIR Study of Heterogeneous Oxidation of SOA Tracers by Ozone - Wang, Runhua; Huang, Yajuan; Hu, Qian; Cao, Gang; Zhu, Rongshu (Frontiers in Environmental Chemistry, 2021)
Secondary organic aerosols (SOA) play an important role in global climate change and air quality, and SOA tracers can directly characterize the source and reaction mechanism of SOA. However, it is not well known that whether the tracers can be oxidized or how the instability of the tracers in the atmosphere. In this paper, in-situ FTIR was used to analyze the chemical structure changes of erythritol, analogue of 2-methyl erythritol (AME) that is a tracer of isoprene SOA, and 2, 3-dihydroxy-4-oxopentanoic acid (DHOPA), a tracer of toluene SOA, when exposed to high concentration of ozone for short periods. Under the condition of 20 ppm ozone exposure for 30 min, the change rate of absorption area of AME at 3480 and 1700 cm-1 was -0.0134 and 0.00117 int.abs/s, respectively, and the change rate of the absorption area of DHOPA at 1640 and 3340cm-1 was -0.00191 and 0.00218 int.abs/s, respectively. The pseudo-first-order reaction rate constant kapp were 1.89×10-8 s-1 and 2.12×10-7 s-1, and the uptake coefficients of ozone on the surface of AME and DHOPA were (1.3 ± 0.8) ×10-8 and (4.5 ± 2.7) ×10-8, respectively.